(untitled) (International Journal of Food and Nutritional Sciences, 2022)
To assess growth and dietary effectiveness, bivoltine silkworm race (CSR2 x CSR4) fifth instar larvae were raised under a variety of nutrient and environmental stress settings. Data were compared with a control group that received conventional food and was raised in ideal conditions of humidity and temperature. The control group had significantly higher levels of nutritional indices such ingesta, digesta, approximate digestibility %, and reference ratio as well as measurements of larval weight, silk gland weight, cocoon weight, shell weight, and other weights. The majority of these factors were much lower in larvae raised in high-temperature, low-humidity environments. However, treated batches had higher values for the majority of feed conversion efficiency measures as well as the ingesta and digesta needed to create one gramme of cocoon and shell. This may be the result of the larvae’s physiological response to various stress circumstances.